2012
DOI: 10.1371/journal.pone.0029940
|View full text |Cite
|
Sign up to set email alerts
|

Natural Amyloid-Beta Oligomers Acutely Impair the Formation of a Contextual Fear Memory in Mice

Abstract: Memory loss is one of the hallmark symptoms of Alzheimer's disease (AD). It has been proposed that soluble amyloid-beta (Abeta) oligomers acutely impair neuronal function and thereby memory. We here report that natural Abeta oligomers acutely impair contextual fear memory in mice. A natural Abeta oligomer solution containing Abeta monomers, dimers, trimers, and tetramers was derived from the conditioned medium of 7PA2 cells, a cell line that expresses human amyloid precursor protein containing the Val717Phe fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…Disturbances in sleep across many species, including flies, mice, and humans, have been shown to cause cognitive impairment and memory deficits (Graves et al, ; McDermott et al, ; Ganguly‐Fitzgerald et al, ; Abel et al, ; Goel et al, ). Aβ accumulation is also believed to cause cognitive deficits across these species (Iijima et al, ; Lesne et al, , ; Kittelberger et al, ). It has been shown that circadian rhythms are affected by neural expression of Aβ in flies while the molecular clock remains intact (Chen et al, ), suggesting that Aβ may influence other behaviors, such as sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in sleep across many species, including flies, mice, and humans, have been shown to cause cognitive impairment and memory deficits (Graves et al, ; McDermott et al, ; Ganguly‐Fitzgerald et al, ; Abel et al, ; Goel et al, ). Aβ accumulation is also believed to cause cognitive deficits across these species (Iijima et al, ; Lesne et al, , ; Kittelberger et al, ). It has been shown that circadian rhythms are affected by neural expression of Aβ in flies while the molecular clock remains intact (Chen et al, ), suggesting that Aβ may influence other behaviors, such as sleep.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that Aβ causes an age‐dependent memory decline (Westerman et al, ; Lesné et al, ; Kittelberger et al, ), but the exact mechanisms underlying this cognitive dysfunction remain under debate. Unlike their WT littermates, Tg2576 mice suffer a deterioration of synaptic plasticity with age (Chapman et al, ; Jacobsen et al, ; Mitchell et al, ; Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were conducted with conditioned freezing chambers (Coulbourn Instruments) following a similar protocol recently published (Kittelberger et al, 2012). Wild-type C57BL/6 mice (2 months of age) received 2 l of control (CHO medium), 7PA2 CM, or 7PA2 CM in combination with 17-AAG (100 M), via an implanted cannula.…”
Section: Methodsmentioning
confidence: 99%
“…PSD95 is the major scaffolding protein at excitatory synapses and in postsynaptic densities (PSDs) and is crucial for synapse maturation and plasticity (Sheng and Hoogenraad, 2007). The level of PSD95 protein is reduced in AD brains (Gylys et al, 2004), with the degree of reduction correlating with A␤ oligomer levels and the severity of dementia (Love et al, 2006;Proctor et al, 2010). A␤ oligomers have been reported to directly interact with PSD95 at postsynaptic sites (Pham et al, 2010) with the continuous overproduction of A␤ reducing the number and plasticity of local synapses (Wei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation